The Role of the Central Java Provincial Government in Maintaining Land Assets (Supreme Court Case Study Number 3640 K/Pdt/2020) - Ananta, Hafiz Diya (Law Research Review Quarterly, 2024)
Land is an asset that is most sought after and needed as evidenced by the many disputes or conflicts related to land which have become part of social reality in various societies, although with variations in their forms and characteristics. Government agency assets in the form of land are included in government agency assets which are known as Regional Property (BMD). An example of a case related to land ownership is what happened on Jalan Durian Raya, Srondol Wetan Village, Banyumanik District, Semarang City, Central Java Province with a case regarding the struggle for land control between the Central Java Provincial Government vs Yosef Soewarto, in which Yosef Soewarto committed an unlawful act by taking over BMD assets belonging to the Central Java Provincial Government. This research aims to determine the factors that led to the transfer of land assets belonging to the Central Java Provincial Government to Yosef. The research method used is empirical juridical with a qualitative approach. Based on the research results, it can be concluded that the factors that caused the transfer of provincial government assets. Central Java to Yosef Soewarto is the lack of attention from the Central Java Provincial Government in paying attention to and managing its land assets, the existence of parties who want to control these land assets, the lack of security and guarding of these land assets by the Central Java Provincial Government, the involvement of other parties. Efforts made by the Provincial Government. Central Java in getting its assets back is preventive, namely by recording the land assets in KIB A (Land) and repressively. Preventive measures are carried out by recording the land assets in KIB A (Land) and also blocking Yosef Soewarto's certificate. Then, for repressive efforts themselves through trials consisting of first level trials, appeal and cassation levels